Strategy To Improve The Productivity Of The Sakai Sv700tf Compactor By Reducing Unscheduled Engine Breakdowns Due To Low Power In The Fuel System At Pt Amm Jobsite Mifa Bersaudara Mining Area (2024) - Zulfikar, Muhammad; Yato, Yato; Cipta Perdana Hamkaputra, Daeng; Iswanto, Hanif (Indonesian Journal of Multidisciplinary Science, 2025)
One of the compactor models utilized in the mining area of PT Antareja Mahada Makmur site PT MIFA Bersaudara is the Sakai SV700TF Model. The unit model has problems with the fuel system when operated in Indonesia because the actual parts installed and the excisting system still apply Japanese standards as manufacture. The quality of fuel in Indonesia that applies B35 (35% biodiesel) causes many Compactor units to have Low Pressure Engine Fuel problems, causing many Unscheduled Breakdown frequencies. The improvement strategy used in increasing SV700TF productivity is to modify the fuel system lines by installing the SV526D model Water Separator which has a larger filtration volume, well adding fuel additives to improve engine combustion efficiency. The evaluation of the improvement by comparing the frequency of unscheduled low power engine breakdowns before and after the improvement based actual breakdown report data during the trial period. The improvement strategy for the modification of the Sakai SV700TF fuel system compactor lines at the PT AMM site PT MIFA Bersaudara has been proven to reduce the frequency of low power engine breakdowns. The results of this study show that the improvements made have positive impact on engine performance with the result of a decrease in the frequency low power engine breakdown reports by 87% a reduction in lost costs due to clogged filter replacement by 95%. The success of this improvement has increased the productivity of the hauling road maintenance process which has a major impact on the operational productivity process coal hauling.